Estudo clínico controlado da técnica de contenção muscular para correção do sorriso gengival associada ou não ao recontorno gengival e ao uso da toxina botulínica - Teixeira Neto, Alexandre Domingues (2017)
The objective of this interventional clinical research is to evaluate the Muscle Restraint Technique of Upper Lift and Nose Lift Muscle (TCM), associated or not with the gingival recountur (RG) or Botulinum Toxin (TB), through standard clinical and photographic evaluation DSD in Patients with Altered Passive Eruption (EPA) and to measure gingival exposure in patients with gingival smile, evaluating the perspective of clinical outcomes from the patients' point of view. Sixteen patients were included in the study. Patients diagnosed with Altered Passive Eruption (EPA) were included in the Recountur and Muscle group (RM - patients submitted to RG by osteotomy-associated flap surgery and subsequent MBT surgery) (n = 8). Patients without EPA were distributed in the groups Muscle (M - patients submitted only to MCT surgery) (n = 4) and Muscle and Botulinum Toxin group (MTB - patients submitted to previous subcutaneous application (15 days before) for TB and subsequent surgery TCM) (n = 4). Gingival margin measurements were performed up to the lower lip line to evaluate the Clinical Gingival Exposure (EGC) with periodontal probe and Virtual Gingival Exposure (EGV) in photographs using the Digital Smile Design (DSD) standard at the time of 30, 90 and 180 postoperative days. Patients completed the modified VAS scale. Data were submitted to statistical analysis (t-Student, one-way ANOVA and Mann Whitney), with a significance level of 0.05. There was no statistically significant difference between EGC and EGV in any of the postoperative groups and times. In the reduction of EGC in mm (p = 0.098), a statistically significant difference was not found between the groups and postoperative times. In the RM group the mean EGC reduction was 4.15 mm corresponding to 55.09% reduction at 180 days. In group M the mean EGC reduction was 1.93 mm corresponding to 40.84% reduction at 180 days. In the MTB group the mean EGC reduction was 2.62 mm corresponding to 39.57% reduction at 180 days. By the VAS scale there was a significant improvement in the perception of results (p = 0.002) in the RM Group. It was concluded that the TCM was effective and reduced the gingival exposure without statistical difference associated with the RG and TB technique. Clinical and photographic evaluation (DSD) proved to be reliable because clinical and virtual measures did not present statistical differences between them